Hemispheric Asymmetry and Atypical Lobar Progression of Alzheimer-Type Tauopathy. Issue 3 (22nd February 2022) - Tremblay, Cécilia; Serrano, Geidy E; Intorcia, Anthony J; Curry, Jasmine; Sue, Lucia I; Nelson, Courtney M; Walker, Jessica E; Glass, Michael J; Arce, Richard A; Fleisher, Adam S; Pontecorvo, Michael J; Atri, Alireza; et al.
Abstract: The spread of neurofibrillary tau pathology in Alzheimer disease (AD) mostly follows a stereotypical pattern of topographical progression but atypical patterns associated with interhemispheric asymmetry have been described. Because histopathological studies that used bilateral sampling are limited, this study aimed to assess interhemispheric tau pathology differences and the presence of topographically atypical cortical spreading patterns. Immunohistochemical staining for detection of tau pathology was performed in 23 regions of interest in 57 autopsy cases comparing bilateral cortical regions and hemispheres. Frequent mild (82% of cases) and occasional moderate (32%) interhemispheric density discrepancies were observed, whereas marked discrepancies were uncommon (7%) and restricted to occipital regions. Left and right hemispheric tau pathology dominance was observed with similar frequencies, except in Braak Stage VI that favored a left dominance. Interhemispheric Braak stage differences were observed in 16% of cases and were more frequent in advanced (IV–VI) versus early (I–III) stages. One atypical lobar topographical pattern in which occipital tau pathology density exceeded frontal lobe scores was identified in 4 cases favoring a left dominant asymmetry. We speculate that asymmetry and atypical topographical progression patterns may be associated with atypical AD clinical presentations and progression characteristics, which should be tested by comprehensive clinicopathological correlations.